Modulation of mammalian circadian rhythms by tumor necrosis factor-α - Paladino, Natalia (2014)
Systemic low doses of the endotoxin lipopolysaccharide (LPS, 100 µg/kg) administered during the early night induce phase-delays of locomotor activity rhythms in mice. Our aim was to evaluate the role of tumor necrosis factor (Tnf)-alpha and its receptor 1/p55 (Tnfr1) in the modulation of LPS-induced circadian effects on the suprachiasmatic nucleus (SCN). We observed that Tnfr1-defective mice (Tnfr1 KO), although exhibiting similar circadian behavior and light response to that of control mice, did not show LPS-induced phase-delays of locomotor activity rhythms, nor LPS-induced cFos and Per2 expression in the SCN and Per1 expression in the paraventricular hypothalamic nucleus (PVN) as compared to wild-type (WT) mice. We also analyzed Tnfr1 expression in the SCN of WT mice, peaking during the early night, when LPS has a circadian effect. Peripheral inoculation of LPS induced an increase in cytokine/chemokine levels (Tnf, Il-6 and Ccl2) in the SCN and in the PVN. In conclusion, in this study, we show that LPS-induced circadian responses are mediated by Tnf. Our results also suggest that this cytokine stimulates the SCN after LPS peripheral inoculation; and the time-related effect of LPS (i.e. phase shifts elicited only at early night) might depend on the increased levels of Tnfr1 expression. We also confirmed that LPS modulates clock gene expression in the SCN and PVN in WT but not in Tnfr1 KO mice.